REVIEW: MEDICINAL PLANTS WITH PHARMACOLOGICAL ACTIVITY AS ANTIPYRETIC - Nurdiani Adiningsih; Dika Pramita Destiani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Fever is a medical condition characterized by an increased body temperature beyond the normal range of 36 â€“ 37Â°C. If not managed appropriately, fever may lead to complications in therapy. The conventional treatment for fever involves using antipyretics such as paracetamol/acetaminophen, and ibuprofen. However, prolonged use of these synthetic medications may have adverse side effects. Consequently, more patients are turning to herbal medicine to manage fever. This review aims to identify medicinal plants with pharmacological activity as antipyretics. We conducted a systematic literature review using Google Scholar as the search engine database. Our search keywords were â€œtanaman herbalâ€, â€œantipiretik